Search for heavy particles decaying into top-quark pairs using lepton-plus-jets events in proton-proton collisions at √s=13 TeV with the ATLAS detector - Aaboud, Morad; Baas, Alessandra Edda; Bolz, Arthur; Brandt, Oleg; Britzger, Daniel; Djuvsland, Julia Isabell; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; et al. (The European physical journal. C, Particles and fields, 2018)
A search for new heavy particles that decay into top-quark pairs is performed using data collected from proton-proton collisions at a centre-of-mass energy of 13 TeVTeV\text {TeV} by the ATLAS detector at the Large Hadron Collider. The integrated luminosity of the data sample is 36.1 fb−1−1^{-1}. Events consistent with top-quark pair production are selected by requiring a single isolated charged lepton, missing transverse momentum and jet activity compatible with a hadronic top-quark decay. Jets identified as likely to contain b-hadrons are required to reduce the background from other Standard Model processes. The invariant mass spectrum of the candidate top-quark pairs is examined for local excesses above the background expectation. No significant deviations from the Standard Model predictions are found. Exclusion limits are set on the production cross-section times branching ratio for hypothetical Z′Z′Z' bosons, Kaluza-Kein gluons and Kaluza-Klein gravitons that decay into top-quark pairs.
ATLAS Collaboration: M. Aaboud, A.E. Bolz, A.E. Baas, O. Brandt, D. Britzger, J.I. Djuvsland, M. Dunford, D.E. Ferreira de Lima, S. Franchino, M.P. Geisler, M. Giulini, P. Hanke, J. Jongmanns, M. Kolb, A. Kugel, M. Lisovyi, H. Meyer Zu Theenhausen, F. Napolitano, D.I. Narrias Villar, M. Sahinsoy, A. Schoening, H-C. Schultz-Coulon, D. Sosa, T.M. Spieker, R. Stamen, P. Starovoitov, S. Suchek, S.M. Weber, M. Wessels [und weitere]
Gesehen am 08.04.2019